2017
DOI: 10.1016/j.tetlet.2017.05.084
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase synthesis of cyclic hexapeptides wollamides A, B and desotamide B

Abstract: Solid-phase synthesis of antibacterial cyclohexapeptides including wollamides A, B and desotamide B has been developed. Briefly, the protected linear hexapeptides were assembled on 2-chlorotrityl chloride resin using standard Fmoc chemistry and diisopropylcarbodiimide/hydroxybenzotriazole coupling reagents, cleaved off-resin with hexafluoroisopropanol/dichloromethane to keep side-chain protecting groups intact, and cyclized in solution. Final global removal of all protecting groups using a cocktail of trifluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Wollamide-producing Streptomyces species are exceptionally rare and to the best of our knowledge cannot be sourced from existing repositories (i.e., the ATCC). Our initial identification of the synthetically accessible antimycobacterial cyclic hexapeptide wollamides (8) have led to reports on the chemical synthesis of wollamides (9,11,12) and SAR investigations against M. tuberculosis H37Rv (11,12). The present study assessed 36 new synthetic wollamides and compared their structure-activity relationships to those of 46 known cyclic peptide wollamide derivatives.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wollamide-producing Streptomyces species are exceptionally rare and to the best of our knowledge cannot be sourced from existing repositories (i.e., the ATCC). Our initial identification of the synthetically accessible antimycobacterial cyclic hexapeptide wollamides (8) have led to reports on the chemical synthesis of wollamides (9,11,12) and SAR investigations against M. tuberculosis H37Rv (11,12). The present study assessed 36 new synthetic wollamides and compared their structure-activity relationships to those of 46 known cyclic peptide wollamide derivatives.…”
Section: Discussionmentioning
confidence: 98%
“…Preliminary structure-activity relationship (SAR) studies, comparing the naturally produced wollamides and desotamides, highlighted the importance of amino acid residue VI (i.e., D-Orn over Gly) and suggested that compound 2 held promise. The solid-phase synthesis of compound 2 was subsequently described (9,10), as were SAR studies for some synthetic wollamides, assessing in vitro growth-inhibitory activity against M. tuberculosis H37Rv (11,12). Here, we report the synthesis and antimycobacterial activity of 36 new wollamide analogues and compare their antimycobacterial activity with that of 46 known wollamides.…”
mentioning
confidence: 96%
“…In 2017, our group reported the total synthesis of the natural products wollamides A ( 48 ) and B ( 42 ) and desotamide B ( 49 ) ( Figure 9 ) using SPPS of linear hexapeptide precursors followed by cleavage and solution-phase cyclization [ 45 ]. A representative synthesis that was used to access wollamide B ( 42 ) is highlighted in Scheme 9 .…”
Section: Solid-phase Synthesis Of Cyclohexapeptides Using Solutionmentioning
confidence: 99%
“…An optimization study investigated the efficiency of the macrocyclization step occurring at each of the six peptide bond sites. This determined that macrocyclization of the linear hexapeptide precursor between terminal L-Leu and D-Leu residues provided the most efficient macrocyclization without any detectable epimerization [ 45 ].…”
Section: Solid-phase Synthesis Of Cyclohexapeptides Using Solutionmentioning
confidence: 99%
See 1 more Smart Citation